The Political Economy of Seigniorage - Aisen, Ari (IMF Working Papers; Working Paper ;, 2005)
While most economists agree that seigniorage is one way governments finance deficits, there is less agreement about the political, institutional, and economic reasons for relying on it. This paper investigates the main determinants of seigniorage using panel data on about 100 countries, for the period 1960-1999. Estimates show that greater political instability leads to higher seigniorage, especially in developing, less democratic, and socially polarized countries, with high inflation, low access to domestic and external debt financing and with higher turnover of central bank presidents. One important policy implication of this study is the need to develop institutions conducive to greater economic freedom as a means to lower the reliance on seigniorage financing of public deficits.